OVERCOMING PROBLEMS IN ACCOMPANYING PASTORAL COUNSELING BIPOLAR PATIENTS - Suwito , Tri Prapto; PAP, Yonas (UJoST- Universal Journal of Science and Technology, 2025)
Mental disorders are serious problems that affect many individuals across the world. Poor mental health is often a major risk factor in a person's good name. In an effort to improve the family name, efforts to improve mental problems are always sought by the family. Mental health is an important key that is the center of attention. This study aims to examine the role of mental health as a prevention factor from the worsening condition of schizophrenia patients from the perspective of pastoral counseling. In this study, the pastoral counseling approach is used as a framework to analyze how preventive efforts in the field of mental health can be assisted through the process of mentoring and pastoral counseling support. This approach justifies the complexity of the individual as a being that has spiritual, social, emotional, and physical dimensions. In pastoral counseling, it is important to understand and appreciate the diversity of individuals in order to assess a situation without having to judge. Through pastoral counseling techniques, efforts can be made more familiar because the counselor uses the best way to examine the patient's circumstances and environment and family, while providing emotional support. as well as conducive guidance between counselors and counselors. In the process of pastoral counseling, counselors pay attention to aspects of mental health change and in a holistic way integrate theological understanding and counseling. This research makes an important contribution in helping the role of pastoral counseling in suppressing the increase in bipolar symptoms.